Combination Therapy for Reconstructive Periodontal Treatment in the Lower Anterior Area: Clinical Evaluation of a Case Series - Carlos E. Nemcovsky; Ilan Beitlitum (MDPI AG, 2018)
Clinically, periodontal regeneration may be achieved by the application of barrier membranes, grafts, wound-healing modifiers, and their combinations. Combination therapy refers to the simultaneous application of various periodontal reconstructive treatment alternatives to obtain additive effects. This approach may lead to assemblage of different regenerative principles, such as conductivity and inductivity, space provision and wound stability, matrix development and cell differentiation. The application of autogenous connective tissue grafts during periodontal regenerative treatment with enamel matrix proteins derivative (EMD) has been previously reported. The present case series present a modified approach for treatment of severe periodontally involved lower incisors presenting with thin gingival biotype, gingival recession, minimal attached and keratinized gingiva width and muscle and/or frenum pull. In all cases a combination therapy consisting of a single buccal access flap, root conditioning, EMD application on the denuded root surfaces and a free connective tissue graft was performed. Clinical and radiographic outcomes were consistently satisfactory, leading to probing depth reduction, clinical attachment gain, minimal gingival recession, increased attached and keratinizing gingival width, elimination of frenum and/or muscle pull together with radiographic bone fill of the defects. It may be concluded that the present combination therapy for reconstructive periodontal treatment in the lower anterior area is a valuable alternative for indicated cases.